KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA GURU (KAJIAN DARI ASPEK ONTOLOGI) - Anitia Fadhila Bumay; Sudjarwo, Sudjarwo; Muhammad Nurwahidin; Bujang Rahman (Jurnal Cakrawala Ilmiah, 2022)
This article aims to examine from the ontological aspect the role of the school principal on teacher performance. Literature review is the method used in this study where data collection was carried out using articles collected from 2017 to 2022. The reference articles were 15 national articles obtained from Google Scholar with the search "transformational leadership" and "teacher performance". The theoretical benefit of this article is to increase knowledge on the ontology of transformational leadership and teacher performance, then the practical benefit of this article can be used as a reference for further research. The conclusion in this article is that transformational leadership plays a major role in teacher performance.